Ligand Modulation of Active Sites to Promote Electrocatalytic Oxygen Evolution. Issue 18 (4th April 2022) - Huang, Wenzhong; Li, Jiantao; Liao, Xiaobin; Lu, Ruihu; Ling, Chaohong; Liu, Xiong; Meng, Jiashen; Qu, Longbing; Lin, Mengting; Hong, Xufeng; Zhou, Xunbiao; Liu, Shanlin; et al.
Abstract: Rationally designed catalysts hold the key to address the sluggish kinetics of oxygen evolution reaction (OER). However, engineering the active sites of such catalysts still faces grand challenges. This study proposes a feasible ligand modulation strategy to boost the OER catalytic activity of cobalt‐iron oxyhydroxide ((Fe, Co)OOH). The 2‐methylimidazole (MI) ligand coordination on (Fe, Co)OOH reduces the orbital overlap between the Fe/Co 3d and O 2p, which weakens the adsorption to oxygen‐containing intermediates and thus facilitates the unfavorable O2 desorption. As a result, the MI ligand modulated (Fe, Co)OOH achieves an excellent OER performance with low overpotentials (230/290 mV at 10/100 mA cm ‐2 ) and excellent durability (>155 h). This study provides a novel ligand modulation strategy for the design of OER catalysts. Abstract : Benefiting from the 2‐methylimidazole (MI) ligand modulated electronic structure, the (Fe, Co)OOH/MI reduces the orbital overlap between the Fe/Co 3d and O 2p, which weakens the adsorption to oxygen‐containing intermediates and thus facilitates the unfavorable O2 desorption. As a result, the MI‐modulated catalyst demonstrates ultralow overpotential (230/290 mV at 10/100 mA cm ‐2 ), and robust stability (>155 h).